Dampak Zakat dan Wakaf Terhadap Pembangunan Sosial Ekonomi : Bukti Dari Negara - Karmilah; Fazli; Rudi Setiawan; I Putu Anjas Jaya Kusuma; Fauzan Redondo Eko (CV. Doki Course and Training, 2025)
ABSTRACT Economic development is something that is expected to be sustainable because development expects a better goal, for that in starting development from a physical and non-physical perspective requires one of them funding for its smooth running. While the existence of funding instruments is currently widespread or not only conventionally but there are sharia concepts including zakat, waqf and sukuk which have led to many developments. This research aims to discuss how zakat, waqf and sukuk as sharia concept funding and their optimization as funding in economic development. With a qualitative method of literature study, it is found that zakat, waqf and sukuk are considered as sharia funding with the concept of contracts and operations managed by related institutions in accordance with sharia and have been applied from the reign of the Islamic Caliphate. The optimization of the three instruments starts from the expertise of zakat management institutions in spreading understanding of the three instruments and establishing regulations that make it easier for people to submit zakat, waqf and invest in sukuk, as well as developing new types or processes in zakat waqf and sukuk such as zakat as a source of investment, cash waqf, green sukuk and blue sukuk for economic growth. Abstrak Pembangunan ekonomi merupakan sesuatu yang diharapkan keberlanjutannya karena pembangunan itu mengharapkan tujuan kearah yang lebih baik, untuk itu dalam memulai pembangunan dari segi fisik dan non fisik membutuhkan salah satunya pendanaan untuk kelancarannya. Sementara keberadaan instrument pendanaan saat ini sudah meluas atau tidak secara konvensional saja melainkan ada konsep syariah diantaranya zakat, wakaf dan sukuk yang memunculkan banyak perkembangan. Penelitian ini bertujuan membahas tentang bagaimana zakat, wakaf dan sukuk sebagai pendanaan berkonsep syariah dan optimalisasinya sebagai pendanaan dalam pembangunan ekonomi. Dengan metode kualitatif studi Pustaka didapat bahwa zakat, wakaf dan sukuk dinilai sebagai pendanaan syariah dengan konsep akad dan operasionalnya yang dikelola oleh lembaga terkait sesuai syariah dan sudah diterapkan dari masa pemerintahan kekhalifahan Islam. Optimalisasi ketiga instrument tersebut dimulai dari kepiawaian lembaga pengelola zakat dalam menyebarkan pemahaman tentang ketiga instrument tersebut serta menetapkan regulasi yang mempermudah masyarakat dalam menyerahkan zakat, berwakaf dan berinvestasi sukuk, serta mengembangkan jenis atau proses baru dalam zakat wakaf.